Bioresorbable ureteral stents from natural origin polymers - Barros, Alexandre A. (2015)
In this work, stents were produced from natural originpolysaccharides. Alginate, gellan gum, and a blend ofthese with gelatin were used to produce hollow tube (stents)following a combination of templated gelation and criticalpoint carbon dioxide drying. Morphological analysis of thesurface of the stents was carried out by scanning electronmicroscopy. Indwelling time, encrustation, and stability ofthe stents in artificial urine solution was carried out up to 60days of immersion. In vitro studies carried out with simulatedurine demonstrated that the tubes present a high fluid uptakeability, about 1000%. Despite this, the materials are able tomaintain their shape and do not present an extensive swellingbehavior. The bioresorption profile was observed to behighly dependent on the composition of the stent and it canbe tuned. Complete dissolution of the materials may occurbetween 14 and 60 days. Additionally, no encrustation wasobserved within the tested timeframe. The ability to resistbacterial adherence was evaluated with Gram-positive Staphylococcus aureus and two Gram-negatives Escherichia coliDH5 alpha and Klebsiella oxytoca. For K. oxytoca, no differenceswere observed in comparison with a commercialstent (BiosoftVR duo, Porges), although, for S. aureus alltested compositions had a higher inhibition of bacterialadhesion compared to the commercial stents. In case ofE. coli, the addition of gelatin to the formulations reducedthe bacterial adhesion in a highly significant manner comparedto the commercial stents. The stents produced by thedeveloped technology fulfill the requirements for ureteralstents and will contribute in the development of biocompatible and bioresorbable urinary stents.